Vascular endothelial growth factor suppression times in patients with diabetic macular oedema treated with ranibizumab. Issue 2 (13th November 2013) - Muether, Philipp S; Droege, Katharina M; Fauser, Sascha
Abstract : Background: To measure vascular endothelial growth factor (VEGF) levels in aqueous humour from patients with diabetic macular oedema (DME) treated with ranibizumab and to determine how long VEGF was suppressed. Methods: In this nonrandomised, prospective clinical study, 17 eyes of 17 patients were included in the study. A total of 110 aqueous humour samples were taken before an intravitreal ranibizumab injection in patients with DME. VEGF-A was measured by Luminex multiplex bead analysis (Luminex Inc, USA). Results: VEGF was completely suppressed in all patients after ranibizumab injections for a mean of 33.7 days (SD±5.1, range 27–42, median 34). VEGF suppression times were individually stable during the observation time of up to 16 months. There was no statistically significant difference of VEGF levels at baseline and before the beginning of a new injection series (123.6 pg/mL vs 125.1 pg/mL; p=1.0, Wilcoxon). Conclusions: Monthly ranibizumab injections lead to a complete VEGF suppression in patients with DME. The long-term stability and the range of suppression times among individuals suggest that some patients could benefit from individual injection intervals.